The bone marrow microenvironment is a critical player in the NK cell response against acute myeloid leukaemia in vitro. Issue 2 (February 2015) - Vasold, Jochen; Wagner, Michaela; Drolle, Heidrun; Deniffel, Christian; Kütt, Alexander; Oostendorp, Robert; Sironi, Silvia; Rieger, Christina; Fiegl, Michael
Highlights The bone marrow microenvironment creates a niche for leukemic blasts. This microenvironment comprises inter alia hypoxia and mesenchymal stromal cells. Hypoxia of 1% O2 enhances leukaemia cell lysis by NK cells. Mesenchymal stromal cells protect leukaemia cell from NK cell mediated lysis.